(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores the concepts, types, content, and significance of presumption and prejudice in the legal system, along with their positive and negative aspects. It analyzes the views and opinions previously put forward by legal experts and scholars on presumption and prejudice. Furthermore, it highlights how these concepts acquire importance within legal families.